Clinical and economic burden of community-onset multidrug-resistant infections requiring hospitalization. Issue 3 (March 2020) - López-Montesinos, I.; Domínguez-Guasch, A.; Gómez-Zorrilla, S.; Duran-Jordà, X.; Siverio-Parès, A.; Arenas-Miras, M.M.; Montero, M.M.; Sorli Redó, L.; Grau, S.; Horcajada, J.P.
Highlights: Community-onset multidrug-resistant (MDR) infections are increasing. Clinical and economic burden of community-onset MDR infections were evaluated. Community-onset MDR infections had longer hospital stay and higher costs. Multidrug resistance was related to sicker patients and thus to worse outcomes. Multidrug resistance could be a marker of more complicated and expensive admissions. Summary: Objectives: To analyze the clinical and economic burden of community-acquired (CA) or community-onset healthcare-associated (COHCA) multidrug-resistant (MDR) infections requiring hospitalization. Methods: Case-control study. Adults admitted with CA or COHCA MDR infections were considered cases, while those admitted in the same period with non-MDR infections were controls. The matching criteria were source of infection and/or microorganism. Primary outcome was 30-day clinical failure. Secondary outcomes were 90-day and 1-year mortality, hospitalization costs and resource consumption. Results: 194 patients (97 cases and 97 controls) were included. Multivariate analysis identified age (odds ratio [OR], 1.07, 95% confidence interval [CI], 1.01–1.14) and SOFA score (OR, 1.45, CI95%, 1.15–1.84) as independent predictors of 30-day clinical failure. Age (hazard ratio [HR] 1.09, 95%CI, 1.03–1.16) was the only factor associated with 90-day mortality, whereas age (HR 1.06, 95%CI, 1.03–1.09) and Charlson Index (HR 1.2, 95%CI, 1.07–1.34) were associated with 1-year mortality. MDR group showed longer hospitalization ( p <0.001) and MDR hospitalization costs almost doubled those in the non-MDR group. MDR infections were associated with higher antimicrobial costs. Conclusions: Worse economic outcomes were identified with community-onset MDR infections. MDR was associated with worse clinical outcomes but mainly due to higher comorbidity of patients in MDR group, rather than multidrug resistance.